Co-administration of temozolomide (TMZ) and the experimental therapeutic targeting miR-10b, profoundly affects the tumorigenic phenotype of human glioblastoma cells - Ming Chen; Ming Chen; Bryan Kim; Bryan Kim; Neil Robertson; Neil Robertson; Sujan Kumar Mondal; Sujan Kumar Mondal; Zdravka Medarova; Anna Moore; Anna Moore (Frontiers in Molecular Biosciences, 2023)
Introduction: Recent studies have shown that miRNA-10b is highly expressed in high-grade glioblastoma multiforme (GBM), and its inhibition leads to deregulation of multiple pathways in tumorigenesis, resulting in repression of tumor growth and increased apoptosis. Thus, we hypothesized that suppressing miR-10b could enhance the cytotoxicity of conventional GBM chemotherapy with temozolomide (TMZ).Methods: Inhibition of miR-10b in glioblastoma cells was achieved using an experimental therapeutic consisting of anti-miR10b antagomirs conjugated to iron oxide nanoparticles (termed MN-anti-miR10b). The nanoparticles serve as delivery vehicles for the antagomirs as well as imaging reporters guiding the delivery in future animal studies.Results: Treatment of U251 and LN229 human glioblastoma cells with MN-anti-miR10b led to inhibition of miR-10b accompanied by repression of growth and increase in apoptosis. We next explored whether MN-anti-miR10b could enhance the cytotoxic effect of TMZ. During these studies, we unexpectedly found that TMZ monotherapy increased miR-10b expression and changed the expression of corresponding miR-10b targets. This discovery led to the design of a sequence-dependent combination treatment, in which miR-10b inhibition and induction of apoptosis by MN-anti-miR10b was followed by a sub-therapeutic dose of TMZ, which caused cell cycle arrest and ultimately cell death. This combination was highly successful in significant enhancement of apoptosis and decrease in cell migration and invasiveness.Discussion: Considering the unexpected effects of TMZ on miR-10b expression and possible implications on its clinical application, we reasoned that comprehensive in vitro studies were warranted before embarking on studies in animals. These intriguing findings serve as a solid foundation for future in vivo studies and offer promise for the successful treatment of GBM.